"Many women use contraceptives in secret": a qualitative study of health provider perspectives regarding barriers and enablers to reproductive health and antenatal care services in rural Tanzania - Melinda Chelva; Sidonie Chard; Alexa Eberle; Alexandra Lucchese; Sanchit Kaushal; Nicola West; Prisca Dominic Marandu; Graeme Smith; Erica Erwin; Robert Philemon Tillya; Anna Nswilla; Karen Yeates (Inishmore Laser Scientific Publishing Ltd, 2022)
# Background Women in sub-Saharan Africa face numerous barriers to reproductive health and antenatal care (ANC) services. The objective of this study was to identify health provider perspectives regarding the barriers and enablers to reproductive health, ANC, and postnatal care (PNC) services in rural Tanzania. # Methods A qualitative study was conducted in four districts of Tanzania and utilized key informant interviews (KIIs) and focus group discussions (FGDs). An interview guide was developed, focusing on individual and community-based factors (barriers and enablers) to accessing ANC and PNC services. Data were collected during December 2017 and May 2018 and analyzed using a thematic approach. # Results Two major themes were identified as barriers to women accessing ANC and PNC services. First, factors related to women in the context of their family and community, for example (i) lack of autonomy in a patriarchal society, (ii) lack of knowledge and education regarding healthy pregnancy and pregnancy complications, (iii) lack of financial resources or control over financial resources, (iv) use of traditional birth attendants, (v) lack of male involvement, (vi) cultural beliefs as barriers to accessing family planning and ANC and PNC services. Second, factors present in the health system, for example (i) lack of infrastructure, equipment and health provider resources at health facilities, and (ii) lack of confidentiality and feelings of stigmatization when receiving health services. Reduced stigmatization against women with Human Immunodeficiency Virus (HIV) served as an enabler. # Conclusions Overall, this study highlights the need to implement more initiatives in these rural districts to improve ANC and PNC services uptake. It also indicates the need to find strategies to improve male involvement and family support in the local context.